Empirical multimodality research methods, evaluations, implications - Bateman, John A.; Boesen, Kristoffer Claussen; Ewerth, Ralph; Hiippala, Tuomo; Jiang, Zhanhao; Johannessen, Christian Mosbæk; Kang, Jiaping; Kessell, Angela; Kiaer, Jieun; Kim, Loli; Müller-Budack, Eric; Otto, Christian; et al. (De Gruyter, 2021)
This volume advances the data-based study of multimodal artefacts and performances by showcasing methods and results from the latest endeavors in empirical multimodal research, representing a vibrant international and interdisciplinary research community. The collated chapters identify and seek to inspire novel, mixed-method approaches to investigate meaning-making mechanisms in current communicative artifacts, designs, and contexts; while attending to their immersive, aesthetic, and ideological dimensions. Each contribution details innovative aspects of empirical multimodality research, offering insights into challenges evolving from quantitative approaches, particular corpus work, results from eye-tracking and psychological experiments, and analyses of dynamic interactive experiences. The approaches and results presented foreground the inherent multidisciplinary nature and implications of multimodality, renegotiating concepts across linguistics, media studies, (social) semiotics, game studies, and design. With this, the volume will inform both current and future developments in theory, methods, and transdisciplinary contexts and become a landmark reference for anyone interested in the empirical study of multimodality.